Oxygen Uptake and Bilaterally Measured Vastus Lateralis Muscle Oxygen Desaturation Kinetics in Well-Trained Endurance Cyclists - Karmen Reinpõld; Indrek Rannama (Journal of Functional Morphology and Kinesiology, 2023)
The aim of the present study was to compare and analyse the relationships between pulmonary oxygen uptake and vastus lateralis (VL) muscle oxygen desaturation kinetics measured bilaterally with Moxy NIRS sensors in trained endurance athletes. To this end, 18 trained athletes (age: 42.4 ± 7.2 years, height: 1.837 ± 0.053 m, body mass: 82.4 ± 5.7 kg) visited the laboratory on two consecutive days. On the first day, an incremental test was performed to determine the power values for the gas exchange threshold, the ventilatory threshold (VT), and V̇O2max levels from pulmonary ventilation. On the second day, the athletes performed a constant work rate (CWR) test at the power corresponding to the VT. During the CWR test, the pulmonary ventilation characteristics, left and right VL muscle O2 desaturation (DeSmO2), and pedalling power were continuously recorded, and the average signal of both legs’ DeSmO2 was computed. Statistical significance was set at p ≤ 0.05. The relative response amplitudes of the primary and slow components of VL desaturation and pulmonary oxygen uptake kinetics did not differ, and the primary amplitude of muscle desaturation kinetics was strongly associated with the initial response rate of oxygen uptake. Compared with pulmonary O2 kinetics, the primary response time of the muscle desaturation kinetics was shorter, and the slow component started earlier. There was good agreement between the time delays of the slow components describing global and local metabolic processes. Nevertheless, there was a low level of agreement between contralateral desaturation kinetic variables. The averaged DeSmO2 signal of the two sides of the body represented the oxygen kinetics more precisely than the right- or left-leg signals separately.